Intrastromal Injection of Bevacizumab in the Management of Corneal Neovascularization: About 25 Eyes - Belghmaidi Sarah; Hajji Ibtissam; Baali Mohammed; Soummane Hasna; Moutaouakil Abdeljalil (Journal of Ophthalmology)
Introduction. Corneal neovessels are a major risk factor for corneal graft rejection, due to the loss of the immune privilege. The purpose of this study is to evaluate the effectiveness of intrastromal injection of bevacizumab in the treatment of corneal neovascularization. Material and Methods. This is a prospective study that included 25 eyes of 22 patients with deep corneal neovessels, treated with intrastromal injections of bevacizumab. Results. The average age of patients was 31 years ranging from 16 to 44 years. The causes of neovascularization were dominated by herpetic keratitis (10 cases). The evolution was marked by complete regress of neovessels in 16 patients, partial regress in 6 cases, and reduced opacity and improved visual acuity in 5 patients. No side effects were noted. Discussion. Short-term results demonstrated the effectiveness of intrastromal injection of bevacizumab in the treatment of corneal neovessels. It may be an option or a complement to other useful treatments in stabilizing or improving vision. Conclusion. Bevacizumab is an effective additional treatment for the improvement of corneal transplants prognosis with preoperative corneal neovascularization.